2003
DOI: 10.1118/1.1582470
|View full text |Cite
|
Sign up to set email alerts
|

Flat panel detector‐based cone beam computed tomography with a circle‐plus‐two‐arcs data acquisition orbit: Preliminary phantom study

Abstract: Cone beam computed tomography (CBCT) has been investigated in the past two decades due to its potential advantages over a fan beam CT. These advantages include (a) great improvement in data acquisition efficiency, spatial resolution, and spatial resolution uniformity, (b) substantially better utilization of x-ray photons generated by the x-ray tube compared to a fan beam CT, and (c) significant advancement in clinical three-dimensional (3D) CT applications. However, most studies of CBCT in the past are focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…System parameters, including optimized spectra and gantry geometry, have been extensively investigated by several research groups. 25,[27][28][29][30][31][32] An initial clinical study suggests that the cone beam breast CT is significantly better than mammography for visualization of soft tissue lesions. 26 A recent clinical study has also shown that breast CT has a significantly lower anatomical noise than mammography and breast tomosynthesis, providing the ultimate solution to eliminate the anatomical noise induced by overlap of the breast tissue.…”
Section: Introductionmentioning
confidence: 99%
“…System parameters, including optimized spectra and gantry geometry, have been extensively investigated by several research groups. 25,[27][28][29][30][31][32] An initial clinical study suggests that the cone beam breast CT is significantly better than mammography for visualization of soft tissue lesions. 26 A recent clinical study has also shown that breast CT has a significantly lower anatomical noise than mammography and breast tomosynthesis, providing the ultimate solution to eliminate the anatomical noise induced by overlap of the breast tissue.…”
Section: Introductionmentioning
confidence: 99%
“…First results on experimental CT systems combining cone-beam CT scanners and FPD technology have been published recently [8,19,20]. These results are promising, and development is ongoing.…”
Section: Ex Vivo Feet Specimensmentioning
confidence: 86%
“…Several investigations of simulations, phantom studies, and preliminary patient imaging have shown CBCT to be an imaging tool with superior contrast resolution and sufficient spatial resolution which can potentially result in a higher positive predictive value than mammography in the detection of cancer , Chen, 2003Ning et al, 2001Ning et al, , 2002, Ning, Tang et al, 2003, Ning et al, 2004. High-resolution real-time flat panel detector (FPD) systems have recently been introduced.…”
Section: High-resolution Cone-beam Computed Tomography Breast Imagingmentioning
confidence: 99%